Hubungan Antara Tingkat Stres Kerja dengan Pemilihan Coping Stress Strategy Karyawan di Kantor Pusat Adira Insurance - Johannes A. A. Rumeser; Theodora Elma Tambuwun (Humaniora, 2011)
Business development in Indonesia affects companies’ competitiveness so they must be able to compete and survive to reach their goal. One of the ways is to use the resources well. Employees are one company resources that help to reach the goals, therefore they have a high possibility of having working stress in doing their job in the company. If employess have working stress, they will get ill and cause financial loss to company. This research is purposed to deal with working stress problems by investigate the relation between working stress level and choosing coping stress strategy for employees in Adira Insurance. Samples in this research consist of 30 men respondents, 49 women respondent, and 5 random respondents. This research type is non-experimental, and as correlational research. This research founded that there is positive relationship between working stress level and choosing coping stress strategy for employees in Adira Insurance.